Genomic characterization of multidrug-resistance gene cfr in Escherichia coli recovered from food animals in Eastern China - Tang, Biao; Ni, Juan; Lin, Jiahui; Sun, Yangying; Lin, Hui; Wu, Yuehong; Yang, Hua; Yue, Min (Frontiers in Microbiology, 2022)
The plasmid-borne cfr gene, mediating multiple drug resistance (MDR), has been observed in many Gram-positive bacteria. The prevalence of cfr and its co-occurrence with additional antimicrobial resistance (AMR) determinants in Escherichia coli is an ongoing issue. Additionally, the prevalence and transfer mechanism of the cfr gene remain partially investigated. Here, eight cfr-positive E. coli strains were screened using PCR from an extensive collection of E. coli (n=2,165) strains isolated from pigs and chickens in 2021 in China, with a prevalence rate of 0.37%. All of them were MDR and resistant to florfenicol and tetracycline. These strains can transfer the cfr gene to E. coli J53 by conjugation (1.05×10−1~1.01×10−6). Moreover, the IncX4 plasmid p727A3-62K-cfr (62,717 bp) harbouring cfr in strain EC727A3 was confirmed using Oxford Nanopore Technology. The unknown type plasmid p737A1-27K-cfr (27,742 bp) harbouring cfr in strain EC737A1 was also identified. Notably, it was verified by PCR that three of the eight E. coli strains were able to form the cfr-IS26 circular intermediate. It was 2,365 bp in length in strains EC727A3 and ECJHZ21-173, and 2,022 bp in length in EC737A1. Collectively, this study demonstrated that IS26 plays a vital role in transmitting the MDR gene cfr in E. coli via conjugation and provided updated knowledge regarding cfr in E. coli in Eastern China.